The measurement of radical species of atmospheric importance - Bell, C; Claire Bell (2010)
The measurement of radical species in the atmosphere has far reaching implications. For example, it is necessary to both understand and improve our knowledge of radicals in the atmosphere to better inform the models which in many cases are the best way of predicting future air quality and climate change. Although many of these models are often not fully representative of all the processes occurring, they are the current best estimate based on the knowledge available, and can be useful in informing and directing future policy. The numerous, varied and interlinked cycles in the atmosphere are complex and only by obtaining data on specific species can accurate concentrations be retrieved and fed back into the models to improve their accuracy. This work is concerned with the development and application of an ultrasensitive absorption spectroscopy technique to the problem of detection of the peroxy radical, HO₂. Noise Immune Cavity Enhanced Optical Heterodyne Molecular Spectroscopy (NICE-OHMS) combines cavity enhancement techniques (in order to increase the path length) with frequency and wavelength modulation techniques (in order to reduce the noise). Following a discussion of the current detection methods used by atmospheric scientists to accurately measure and quantitative concentrations, some preliminary work on the detection of ammonia by a simple cavity enhanced absorption setup is presented. Pressure broadening and shift results were obtained for a number of ammonia transitions in the near infrared region, broadened by He, Ne, Ar, Xe, O₂ and N₂. The bulk of the work concentrates on the implementation of the NICE-OHMS technique, presenting the first results with the use of an external cavity diode laser and a ring shaped cavity. A sensitivity of 4 x 10⁻¹¹ cm⁻¹ Hz⁻1/2 is obtained on an individual rovibrational transition of methane at 6610.063 cm⁻¹, along with a selection of other data from the atmospherically important molecules methane, nitrogen dioxide and carbon dioxide, highlighting the broad wavelength range over which the instrument can operate. Finally, the NICE-OHMS technique is used to probe HO₂ radicals formed through the photolysis of a Cl₂/CH₃OH/O₂ mixture. Following the creation and detection of HO₂ radicals in the cavity, and based on the optimum sensitivity outlined above, a minimum concentration of 1 x 10⁹ molecules cm⁻³ has been demonstrated.